Main controlling factors and development patterns of high-quality igneous rock reservoirs in the mesozoic of the Qikou Sag - Chen, Changwei; Li, Hongjun; Pu, Xiugang; Yuan, Haiyue; Dong, Xiaowei; Zhang, Feipeng; Fu, Lixin; Cui, Yu; Li, Haodong (Frontiers in Earth Science, 2025)
The Mesozoic volcanic reservoirs in Qiqikou Sag are complex and diverse. Identifying the characteristics and main controlling factors of high-quality volcanic reservoirs is the key to improve the reserves and production of oil and gas in this area. The establishment of volcanic rock development model provides a reference for further study of volcanic reservoirs. Through core observation, thin section identification, pore permeability and pore structure analysis of volcanic reservoir, combined with production data, on the basis of clarifying reservoir characteristics, the main controlling factors and development modes of high-quality reservoir development are analyzed. The results show that the Mesozoic in Qikou Sag mainly develops neutral andesite and basic basalt of overflow facies, followed by volcanic breccia and tuff of explosive facies. On the whole, the volcanic rock reservoirs belong to high porosity-low permeability and medium porosity-low permeability reservoirs. The physical properties of the andesite reservoir in the overflow phase are the best, showing the characteristics of high porosity-medium permeability. The reservoir space is dominated by secondary pores and fractures, among which dissolution pores are the most important reservoir space types of Mesozoic volcanic reservoirs. Favorable lithofacies and lithology are the foundation for the development of high-quality reservoirs. Favorable lithofacies and lithology are the foundation for the development of high-quality reservoirs, while weathering and dissolution are the key factors for the development of high-quality reservoirs. Fractures further improve the storage performance of igneous rock reservoirs. The dissolution of soluble minerals or volcanic ash in volcanic rocks that have undergone weathering and denudation for a long time produces a large number of secondary dissolution pores. The development of fractures further improves the reservoir physical properties and eventually develops into a weathering crust reservoir. The volcanic rocks far away from the weathering crust increase the reservoir physical properties through the later structural fractures and develop into the inner reservoir.